Anomalous origin of the left brachiocephalic artery in the right aortic arch: Is there a method to the madness? - Krishna, Mani Ram (Ann Pediatr Cardiol, 2017)
The anomalous origin of the left brachiocephalic artery in a right sided aortic arch is a rare vascular ring which might lead to esophageal compression. The exact embryological origin of this anomaly is still widely debated. We present an infant who presented with esophageal compression symptoms and review the various hypotheses about the embryological origin of this anomaly.